MIGRABILITY OF ADDITIVE ( STEARAT ACID AND PALMITAT ACID) IN THE SOLID STATE OF POLYMER - Nasruddin MN; Basuki Wirjosentono; Tulus Tulus; Tjahyono Herawan (Jurnal Dinamis, 2009)
ABSTRACTPoly vinyl Chloride ( PVC) represent materials of thermoplastic as solid polymer conducted in the form of plastic sheet which not yet been mixed with something additive, while other film mixed with additive in the form of oleic acid and Palmitic Acid with comparison 10 : 1; 10 : 2; 10 : 3; and 10 : 4; tested migration testing by arranging in film and pressing between each of PVC and oleic acid, PVC and Palmitic Acid; after that they kept in a place that available and left araund 30 days, then the additive migration of oleic acid into PVC equal to 4.2035 % and the additive of Palmitic to PVC 5.8080 %. From the result obtained the amount of additive migration of oleic acid to is PVC smaller than the additive migration of Palmitic Acid to PVC. It also can be seen that effect of additive migration to solid polymer progressively increase (linearly compass with keeping time).Keyword : Polymer - PVC - Additive - Migration - Time.